Perancangan Presentasi Produk Arsitektur Menggunakan Teknologi Virtual Reality - Andy Satria; Taufik Ahmad; Andreas Natanael Pangaribuan; Jerry Alviansyah (Jurnal Sipil Terapan, 2023)
Presentation in architecture has developed over time. From initially using hand drawings, he then switched to using visuals created by computers. The more technology develops, the more interesting the presentations produced. The results of the presentation also become more realistic so that they are closer to the original design object. Technological developments are increasingly advanced and the use of Virtual Reality technology is widely used in almost all fields, including in the field of architecture. In Architecture, the use of Virtual Reality as a presentation tool has been widely used. However, the method used requires quite a large amount of money and is still too complicated to apply. However, currently Virtual Reality can be done simply and can be applied generally and by architectural practitioners.